Registration Information System for Real Work Practices (PKN) and Thesis Faculty of Engineering, University of Pancamarga - Attijani, Ahmad; Hikmah, Nuzul; Misdiyanto (Universitas Panca Marga, 2022)
A website is a collection of pages containing certain information and can be accessed easily by anyone, anytime, and anywhere through the internet. In an educational institution, of course, it is very necessary for information systems in regulating academic activities that are fast, effective, efficient, accurate to improve the quality standards of education in these educational institutions.Faculty of Engineering, Panca Marga University is one of the private universities in Probolinggo Regency with 3 (three) study programs, namely electrical engineering, mechanical engineering and industrial engineering. Final projects such as Real Work Practice (PKN) and thesis are the final tasks that must be completed by a student who will graduate from the level of undergraduate education or diploma in college.Currently, the final project administration process at the Faculty of Engineering, Panca Marga University is still computerized simply where the final task implementation data is still stored in folders made by academic staff themselves, there is no final project reporting system. This is felt inappropriate so it takes a long time to process the final project data with a large number of students. Based on this, researchers created a pkn final project information system and web-based thesis. In this study, the authors used the Waterfall Method as an application development method. The Waterfall method is a sequential development model. In the process of creating the waterfall method, it starts with analysis, design, coding, testing and maintenance.